Development of Creative Industries Based on Local Wisdom as a Driver of the Tourism Industry - Dhyah Wulansari; Noneng Sukatmadirerja; Susana Merary Romero Benitez (Faculty of Social and Political Science, 2024)
The creative industry is now being focused on by the government as one of the pillars of the Indonesian economy. The mission of the creative industry, among others, is to optimize the development and preservation of local resources that are competitive, dynamic, and sustainable. Local cultural wisdom and abundant natural potential make the growth of the nation's economic support sectors can develop rapidly. The development strategy of local wisdom-based creative industries to support the tourism industry in Nganjuk Regency, especially in the context of the Batik and Ecoprint Center, requires an integrated approach between strengthening local capacity, promotion, and collaboration with the tourism sector. Where tourism activities can be defined by three factors, namely there must be something to see, something to do and something to buy. By implementing these strategies, batik and ecoprint industry centers can not only reach a wider market but also contribute to sustainability goals and become attractive and responsible tourism destinations. The strategy of grouping industries into centers, or clusters, can remain effective to attract markets and support sustainable tourism destinations, especially for industries such as batik and ecoprint, if done appropriately. It also requires the role of the triple helix of government, academia and the business world itself. This triple helix development model will answer the problems faced by the business world, in this case the Batik Center and the Griya Batik Sri Rahayu Ecoprint.